Structural and Theoretical Investigations on the Unique Coloring Scheme of the γ‐Brass Type Phase: Cu5+δCd8‐δ (−1.0≤δ≤0.1). Issue 15 (21st March 2022) - Roy, Nilanjan; Harshit; Mondal, Amit; Wang, Fei; Jana, Partha P.
Abstract: The crystal structure of the γ‐brass type Cu5+δ Cd8‐δ (‐1.0≤δ≤0.1) in the Cu−Cd binary system has been analyzed by powder and single crystal X‐ray diffraction. All the compounds crystallize in the cubic space group I 4 ‾ 3 m (217). Mixing of Cu with Cd leads to a significant phase width. At the limiting composition, a previously unreported ordered compound Cu4 Cd9 is formed. The structure of all compounds is described by a 26‐atom γ‐cluster. Electronic structure calculations on the model structure built according to the ordered "Cu4 Cd9 ", show the presence of a pseudo‐gap at the Fermi level in the electronic density of states, which is consistent with other γ‐brass type phases. However, the site preference of Cu and Cd atoms is different from the other reported γ‐brass type structures in the Zn‐ and Cd‐rich phases. To address the "coloring problem", a series of model structures were constructed with the composition Cu4 Cd9 and their total energies were compared with first‐principle calculations using ABINIT code. LOBSTER package was implemented to extract the bonding information by crystal orbital Hamilton population calculations. Abstract :